Comparison of Escitalopram Alone versus in Combination with Jacobson’s Progressive Muscle Relaxation in Patients with Neurotic, Stress Related and Somatoform Disorders: A Randomised Clinical Study - Piyush Mahajan; Malvika Dahuja; Pranjal Tripathi; Shashank Saurabh Sinha (Journal of Clinical and Diagnostic Research)
Introduction: Anxiety disorders have a prevalence rate of 2.57% and significantly impact well-being and productivity. The course of anxiety disorders is characterised by fluctuating symptom severity, a high relapse rate, and chronicity. Patients with anxiety disorders are typically prescribed antidepressants or anti-anxiety medications, but these treatments often have limited long-term efficacy. Combining pharmacotherapy with non-pharmacological techniques, such as Progressive Muscle Relaxation (PMR), may enhance the effectiveness of treatment for anxiety disorders. Aim: To assess and compare the Hamilton Anxiety Rating Scale (HAM-A) scores at six-month between Group-E (who received Escitalopram exclusively) and Group-E+PMR (who received Escitalopram in addition to PMR). Additionally, the aim was also to compare the baseline HAM-A scores with those obtained after six months within each group. Materials and Methods: A randomised clinical study was conducted in the Department of Psychiatry at Sri Guru Ram Das Institute of Medical Sciences and Research in Amritsar, Punjab, India, from March 2020 to March 2021. The study was carried out following approval from the Institutional Ethics Committee (IEC). Participants were individuals aged 18 to 45 years who visited the Psychiatry Department's Outpatient Department (OPD) and met the ICD-10 criteria for Neurotic, stress-related, and somatoform disorders (F40-F48). One hundred and seventeen participants were randomly allocated to the two groups using a simple randomization method. Group-E received a daily dose of 10 mg Escitalopram for six months, while Group-E+PMR received the same dosage of Escitalopram along with Jacobson’s PMR exercises lasting 20 minutes, twice daily, at their place of residence. The HAM-A scale was employed to assess anxiety levels in both groups. Paired t-tests were conducted to compare pre- and post-treatment HAM-A scores within each group, while independent t-tests were used to compare scores between the groups. Statistical analysis was carried out using SPSS version 24.0 and a significance level of p<0.05 was adopted for the statistical assessments. Results: Both groups were comparable in terms of socio-demographic variables, mean age, and baseline HAM-A scores. The majority of participants, 70 (70%), were females. Significant improvements were noted in the HAM-A scores at six-month mark compared to baseline for both, Group-E and Group-E+PMR (p<0.001). Furthermore, Group-E+PMR exhibited a significant decrease in the HAM-A score at six months compared to Group-E (p<0.001), indicating more substantial improvements. Conclusion: Escitalopram and Escitalopram combined with PMR treatment effectively lowered anxiety. However, the incorporation of PMR Exercises alongside Escitalopram demonstrated more favourable outcomes in individuals with anxiety disorders.